6-Shogaol Inhibits Oxidative Stress-Induced Rat Vascular Smooth Muscle Cell Apoptosis by Regulating OXR1-p53 Axis - Liu, Jing; Li, Bin; Li, Wenlian; Pan, Taowen; Diao, Yunpeng; Wang, Fangjun (Frontiers in Molecular Biosciences, 2022)
Apoptosis of vascular smooth muscle cells (VSMCs) is closely related to the pathogenesis of cardiovascular disease, and oxidative stress is an important cause for VSMCs death. Inhibiting VSMCs apoptosis is an effective preventive strategy in slowing down the development of cardiovascular disease, especially for atherosclerosis. In this study, we found oxidation resistance protein 1 (OXR1), a crucial participator for responding for oxidative stress, could modulate the expression of p53, the key regulator of cell apoptosis. Our results revealed that oxidative stress promoted VSMCs apoptosis by overexpression of OXR1-p53 axis, and 6-shogaol (6S), a major biologically active compound present in ginger, could effectively attenuate cell death by preventing the up-regulated expression of OXR1-p53 axis. Quantitative proteomics analysis revealed that the degradation of p53 mediated by OXR1 might be related with the enhanced assembly of SCF ubiquitin ligase complexes, which is reported to closely relate with the modification of ubiquitination or neddylation, and subsequent degradation of p53.